(untitled) (Research, Society and Development, 2023)
The skin is the organ that protects the internal organism against pathogenic agents from the external environment. Therefore, rapid wound healing becomes an important target against exposure of the organism to pathogens. Thus, the use of biopolymers as dressings has been gaining prominence, among them, chitosan. Chitosan is a biomaterial that has high biological compatibility, biodegradability, low toxicity and healing effect. The objective of this research was to produce a chitosan-based biomaterial, incorporated with a hydroalcoholic extract from the bark of Anacardium microcarpum Ducke. The membranes were characterized in terms of color, homogeneity, flexibility, thickness, wettability and degree of swelling. The membranes were transparent, homogeneous and flexible with an average thickness of 5 micrometers. In swelling, there was absorption of 50%, mass loss below 6% and durability greater than 21 days. As for wettability, the membranes were moderately hydrophilic. The membranes showed promising chemical and physical characteristics to be a curative biomaterial.